Exploring the future application of UAVs: Face image privacy protection scheme based on chaos and DNA cryptography - Heping Wen; Zhiyu Xie; Zhuxi Wu; Yiting Lin; Wei Feng (Journal of King Saud University: Computer and Information Sciences, 2024)
In the application and promotion of UAV in the future, remote sensing image information is transmitted frequently, and its security issues will not be ignored. Aiming at the privacy security problem of portrait information in remote sensing images, this paper proposes a face privacy protection technology scheme based on chaos and DNA cryptography. Firstly, the edge recognition face detection technology is used to identify the face information, and the corresponding matrix is selected as the object of selective encryption. Then, the hash eigenvalues of the selected encrypted object are extracted, and the plaintext-associated chaotic sequences are generated for RGB permutation and zigzag interleaved scrambling in turn. Then, the three channels of RGB are encrypted by dynamic chain DNA encoding in turn. Finally, the cipher-image is obtained after performing discontinuous diffusion and lightweight bit-level confusion. In this paper, chaotic pseudo-random sequences with plaintext correlation and dynamic DNA chain encryption are used to effectively improve the ability of encryption system to resist cryptographic attacks. At the same time, selective encryption can effectively reduce the encryption complexity and performance overhead. Experimental results and security analysis show that the privacy protection scheme has excellent security and efficiency performance. Therefore, the face privacy protection technology scheme reported in this paper has excellent performance and has broad application prospects in UAV and remote sensing communication.